2003
DOI: 10.1242/jcs.00213
|View full text |Cite
|
Sign up to set email alerts
|

A dominant negative form of the AAA ATPase SKD1/VPS4 impairs membrane trafficking out of endosomal/lysosomal compartments: class Evpsphenotype in mammalian cells

Abstract: SKD1 is a member of the family of ATPases associated with cellular activities whose yeast homologue Vps4p has been implicated in endosomal/vacuolar membrane transports. When a mutant of SKD1 that lacks ATPase activity [SKD1(E235Q)] was overexpressed in mammalian cells, it induced a dominant negative phenotype characterized by aberrant endosomal structures (denoted as E235Q compartments). Expression of SKD1(E235Q) caused an accumulation of basolateral recycling receptors, such as asialoglycoprotein receptor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 49 publications
11
120
2
Order By: Relevance
“…Indeed, SPR analysis revealed a stable complex of SBP1-SKD1 in vitro. Previously, we reported that E235Q compartments are derived from multiple endogenous membranes, early and late endosomes, and lysosomes (Fujita et al, 2003). GFP-SKD1(E235Q) co-localizes with several endosomal/lysosomal markers but the extent of the co-localization varies.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, SPR analysis revealed a stable complex of SBP1-SKD1 in vitro. Previously, we reported that E235Q compartments are derived from multiple endogenous membranes, early and late endosomes, and lysosomes (Fujita et al, 2003). GFP-SKD1(E235Q) co-localizes with several endosomal/lysosomal markers but the extent of the co-localization varies.…”
Section: Discussionmentioning
confidence: 97%
“…This result clearly demonstrates that SKD1 and rab5 regulate endosomal membrane transport independently. Interestingly, despite the distinct molecular mechanisms of SKD1(E235Q) and rab5QL, the resultant morphological alterations on late endosomes and lysosomes are quite similar; both induce the enlargement (Fujita et al, 2003;Rosenfeld et al, 2001). Based on our results and those of others, we assume that the biogenesis of lysosomes is highly ascribed to the membrane traffic at early endosomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations